Simulation in In-term-training at the scenes of formation of Primary Health Care - Pavel Vigo Cuza; Bárbara Vitalia León Sánchez; Jaime Segrea González; Tania López Otero; Hivanay F. Martínez López; Celia Ramona León Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: during the last few decades, the health-care professional's process of formation has had an accelerated transformation. No doubts, the use of the simulation in medical teaching has contributed to strengthen the learning process and to raise its quality. Objective: characterizing the knowledge on the simulation and its use the In-term-training for Medicine professors at the scenes of formation of Primary Health Care. Methods: a pedagogic investigation that included 48 professors linked to In-term-training of the Medicine career at the scenes of Primary Health Care; to the ones, an opinion poll was applied. Five informants were interviewed. It was examined: years of experience, knowledge and use of the simulation. Results: it was detected that only the 56, 25 % knows the resource of simulation and only the 48% uses it. The frequency of utilization of the simulation in in-term-training evidenced that the 30, 76% of professors have always used this resource, while the 61.53 % utilizes it only most of the time. Conclusions: The professors present insufficiencies in knowledge on the simulation. Not all the ones that know the simulation utilize it in in-term-training, and those who use it do not do it at all of the spaces or scenes that he propitiates the formation of the General Practitioner in the context of Primary Health Care.